Influence of Risk Management and Income Diversification on Bank Profitability in Indonesia: JEL Classification: G21, G32, E44, G28, M41 - Putri, Vina Kurnia; Edison, Adrian Luthfi; Margaretha Leon , Farah (Newinera Publisher, 2025)
This study aims to examine the effect of risk management and income diversification on the profitability of conventional banks in Indonesia during the 2020–2024 period. Profitability is measured using indicators of operational efficiency and the bank's ability to generate margins through intermediation. The independent variables include credit risk, liquidity risk, bank capital, operational risk, and income diversification as a strategic factor. The research applies a quantitative method with secondary data obtained from the annual financial statements of conventional commercial banks listed on the Indonesia Stock Exchange. The banks were selected using purposive sampling based on data completeness and consistency throughout the observation period. The analysis results show that liquidity risk has a significant negative impact on profitability, while bank capital and operational risk have a significant positive effect. In contrast, credit risk and income diversification do not have a statistically significant influence on profitability. These findings provide an in-depth understanding of how each risk-related variable and income structure aspect contributes to the financial performance of banks. The study concludes that effective risk management and strategic capital utilization play a critical role in improving bank profitability, while income diversification alone may not be sufficient without aligned risk mitigation efforts. This research offers practical implications for bank management in strengthening risk-based decision-making, for investors in assessing financial resilience, and for regulators in formulating stability-focused policies in the national banking sector.